Uncovering the dynamics of individual learning and employee adaptability in influencing innovation behavior - Fauziannor, Fauziannor; Ujianto, Ujianto; Nugroho, Riyadi (Edelweiss Applied Science and Technology, 2024)
The success of organizations in the era of ever-changing business is greatly influenced by the adaptability, creativity, and innovation factors of employees, which are obtained through effective learning. Organizations that implement a learning culture encourage employees to adapt and internalize learning from past experiences. Employees who are active in training become more creative and adaptive, increasing their ability to deal with change. This study aims to explore the relationship between Individual Learning, Employee Adaptability, Employee Creativity, and Employee Innovation Behavior, especially in the State Civil Apparatus (ASN) in South Kalimantan. Through a quantitative approach with analysis using Partial Least Square (PLS), this study found that individual learning significantly affects employee adaptability and creativity, and contributes to their innovative behavior. The results of the study indicate the need for a longitudinal approach to understand the dynamics of changes in employee adaptability and creativity in the context of public services. This study identifies the importance of supporting factors such as management support and work environment that influence employee innovation.